Multicultural Journalism in Documentary Media: A Case Study of Threads of Indonesia - Jolanna Putri Salsabila; Siti Sarifah; Dwi Korina Relawati; Ardian Utomo; Widhihatmini (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2026)
Indonesia, as the world’s largest archipelagic country, is characterized by extensive cultural, ethnic, and religious diversity. This plural social context requires inclusive journalistic practices that respect difference and promote intercultural understanding, as reflected in the principles of multicultural journalism. This study aims to examine how multicultural journalism is applied in the television documentary Threads of Indonesia, particularly in the episode Ngangsu Kawruh Sejatining Urip, which portrays the Pransoeh belief community in Muntilan, Magelang. The study employed a qualitative method with an interpretive approach to explore the community’s worldview and lived experiences. Data were collected through field observation, in-depth interviews with key informants, and documentation of community activities and teachings. The findings show that the documentary applies multicultural journalism through inclusive narration, contextual visual representation, the use of diverse sources, and a non-stereotypical portrayal of the Pransoeh community. The interpretive approach enables the documentary to present minority belief narratives in a respectful and meaningful way while conveying values of tolerance, empathy, and mutual respect. This study contributes to journalism and media studies by extending multicultural journalism beyond conventional news reporting into documentary-based audiovisual storytelling, particularly in representing minority belief communities in Indonesia.